Hubungan Antara Efikasi Diri Dan Kecemasan Pada Mahasiswa Yang Sedang Mengerjakan Skripsi - Priscilla Cloudia Ruth Telussa; Ratriana Y. E. Kusumiati (Academic Journal of Psychology and Counseling, 2022)
Undergraduate thesis is one of the requirements for students to obtain an academic degree. To complete the task, the student must believe in their ability to achieve certain goals which is known as self-efficacy. The study’s objective was to determine the relationship between self-efficacy and anxiety in college students who are working on their undergraduate thesis. The sample in this study was 218 students of the Faculty of Psychology at Universitas Kristen Satya Wacana, chosen with the accidental sampling technique. Data were collected using an online questionnaire in the form of a Google Form. Self-efficacy was measured using the modified General Self-Efficacy Scale (GSES) from Schwarzer & Jerusalem (1993, 2010) and anxiety was measured using the State and Trait Anxiety Inventory (STAI) form YI anxiety scale modified from Spielberger (1989) and Spielberger, Gorsuch, Lushene, Vagg, & Jacobs (1983). Researchers then used Spearman's correlation technique to analyze the data. There was a negative correlation between self-efficacy and anxiety among college students working on their undergraduate theses (r = -0.223, p<0.05). The study concluded that it is necessary to support improvement in self-efficacy in undergraduate students.